1995
DOI: 10.1002/yea.320111408
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular characterization of flor yeasts: Polymorphism of flor yeast populations

Abstract: Yeast strains which form velum on the surface of Sherry wine during the aging process have been isolated and characterized. According to their metabolic and molecular features most of the yeasts that were isolated belong to different races of Saccharomyces cerevisiae (beticus, cheresiensis, montuliensis and rouxii). Due to the conditions under which these yeasts were isolated, all strains have in common the capacity to develop a film as an adaptive mechanism which allows them to grow and survive in 15.5% vol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
2
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 25 publications
3
53
2
1
Order By: Relevance
“…The Saccharomyces strains responsible for sherry wine aging constitute a special group of wine yeasts, which have been poorly studied at a molecular level. In this sense, only one attempt at the molecular characterization of these yeast strains using mtDNA restriction analysis and electrophoretic karyotyping has been made (11,15). In the present study, we have shown, for the first time, the evolution of yeast populations from alcoholic fermentation to biological aging in the production of fino sherry wines.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The Saccharomyces strains responsible for sherry wine aging constitute a special group of wine yeasts, which have been poorly studied at a molecular level. In this sense, only one attempt at the molecular characterization of these yeast strains using mtDNA restriction analysis and electrophoretic karyotyping has been made (11,15). In the present study, we have shown, for the first time, the evolution of yeast populations from alcoholic fermentation to biological aging in the production of fino sherry wines.…”
Section: Discussionmentioning
confidence: 49%
“…Mitochondrial DNA (mtDNA) restriction analysis and karyotyping were used to differentiate strains of S. cerevisiae. Restriction analysis of mtDNA was performed according to the work of Querol et al (19); HinfI was used as the most suitable restriction endonuclease for differentiation among S. cerevisiae flor and nonflor strains (11,15,19). DNA for electrophoretic karyotyping was prepared in agarose plugs as described by Carle and Olson (2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrophoretic karyotypes of wine yeast strains differ in the number, size, and intensity of bands, allowing the identification of every strain by its chromosome pattern (37,40). Wine strains do not have a stable and defined karyotype, like flor yeasts (21), but their variability is not as high as that reported for baker's yeasts (5,10).…”
mentioning
confidence: 99%
“…The early methods related to taxonomy involved morphological studies and biochemical analyses of differences on fermentation and assimilation tests, where the substrates used were mainly dextrose, lactose, maltose, melibiose, raffinose, galactose and sucrose. These physiological properties were traditionally tested using Durham tubes in a liquid medium, which filled up with gas if fermentation occurred [4]. Nevertheless, both morphological and physiological characteristics may be influenced by culture conditions and spoilages and can provide ambiguous results.…”
Section: Introductionmentioning
confidence: 99%